(untitled) - Prof. Dr. Frank Schimmelfennig (Vorsitz), Zürich; Prof. Dr. Thomas Christiansen, Rom; Prof. Dr. Friedrich Heinemann, Mannheim; Prof. Dr. Mathias Jopp, Berlin; Prof. Dr. Friedemann Kainer, Mannheim; Prof. Dr. Michèle Knodt, Darmstadt; Dr. Barbara Lippert, Berlin; Prof. Dr. Hartmut Marhold, Berlin; Prof. Dr. Franz Mayer, Bielefeld; Prof. Dr. Peter-Christian Müller-Graff, Heidelberg; Prof. Dr. Martin Nettesheim, Tübingen; Prof. Dr. Joachim Schild, Trier; et al. (integration, 2023)
Renowned scholars and practitioners discuss current issues of European integration in the areas of political science, law and related fields of research in integration. This journal contains three categories of articles: academic contributions and fundamental analyses of European policy, conference reports and literature reviews. Website: www.integration.nomos.de